Bio-monitoring of Atmospheric Heavy Metals Deposited on Selected Tree Leaves in Kanchipuram, Tamilnadu (Indian Journal of Public Health Research & Development, 2020)
Kanchipuram, one of the holiest cities is highly polluted with heavy metals due to industrialization andurbanization. It is most important to know the role of plants in the cleansing process of heavy metals in thistemple city. In this study, the heavy metals (Fe2+, Pb2+, Cu2+, Zn2+, Al2+, Cd2+, As2+, Cr3+, Mn2+) from thedust deposited on the leaves of the trees were analyzed. The tree species were collected from different zonesof the Kanchipuram town such as residential area, traffic area, Institutional area, hospital area and industrialarea. Heavy metals concentrations were analyzed by inductively coupled plasma mass spectrometry. Mostof the heavy metals were found below their detectable limits (Pb2+, Cd2+, Cu2+, Cr3+, and As2+). Some ofthe heavy metals were in highly increased values (Fe2+, Al2+) almost in selected species. In few locationsthe content of As2+ and Mn2+ in lower levels were deposited on some species. The results obtained fromthe analysis were compared statistically and correlated by using Pearson’s co-efficient. The results obtainedfrom the analysis shown that the heavy metals were emitted from various combustion processes and otheranthropogenic activities. The tree species selected can be used in bio monitoring as bio indicators of increasedFe2+, Al2+ in the ambient air.
Keywords: Heavy metals, Bio Monitoring, Bio Indicators, Species, Deposition, Correlation